Finance and Development, June 1977. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1977)
This paper highlights that IMF activities in the first three months of 1977 were marked by a number of 'firsts.' In addition to approving the largest stand-by arrangement in its history-the SDR 3.36 billion for the United Kingdom-the IMF welcomed its first new member of the year: Guinea-Bissau; held its first gold auction on behalf of the Trust Fund under the new schedule of monthly auctions; made its first loan disbursements as a Trustee of the Trust Fund; and held the first sale of gold for 'restitution.'.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet